2020
DOI: 10.1155/2020/8877334
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of the Expression and Prognostic Significance of P4HA1 in Pancreatic Cancer and Construction of a lncRNA-miRNA-P4HA1 Regulatory Axis

Abstract: Objectives. Prolyl 4-hydroxylase subunit alpha 1 (P4HA1) plays a crucial role in modulating extracellular matrix component and promoting tumor progression by changing tumor adhesion, migration, and other biological behaviors in some cancers. However, its expression pattern, biological function, and underlying mechanism in pancreatic cancer remain largely unclear. Materials and Methods. In this study, a set of bioinformatics tools were used to analyze the expression of P4HA1 and its prognostic value in pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
4
0
2
Order By: Relevance
“…P4HA1 has been found to exert a carcinogenic effect. In esophageal cancer, activation of P4HA1 by STAT1 transcription could boost cell growth and survival (28,29). Zhou et al demonstrated that elevated expression of P4HA1 indicates dismal prognosis in cases with head and neck cancer (HNC).…”
Section: Discussionmentioning
confidence: 99%
“…P4HA1 has been found to exert a carcinogenic effect. In esophageal cancer, activation of P4HA1 by STAT1 transcription could boost cell growth and survival (28,29). Zhou et al demonstrated that elevated expression of P4HA1 indicates dismal prognosis in cases with head and neck cancer (HNC).…”
Section: Discussionmentioning
confidence: 99%
“…По данным Chen T. и соавт., экспрессия miR-335-5p в плазме крови была снижена у пациентов с трижды негативным раком молочной железы по сравнению со здоровым контролем [50], в то время как повышенная экспрессия miR-335-5p приводила к ингибированию ускользания от иммунного ответа, а полное отсутствие miR-335-5p способствовало росту опухоли. В работах на клетках рака поджелудочной железы [51], адренокортикального рака [52] и колоректального рака [53] пониженная экспрессия miR-335-5p была ассоциирована с более неблагоприятным прогнозом заболевания. И наоборот, повышение экспрессии miR-335-5p в основном приводило к снижению пролиферации и миграции опухолевых клеток [53][54][55].…”
Section: Discussionunclassified
“…Gene set variability analysis (GSVA) was used to determine and validate the prognostic signature of the miRNA-based path for PC (miPPSPC) and the prognostic signature of the PC mRNA (mPPSPC) path in independent data sets [91]. MiPPSPPC has been optimized by combining clinical parameters.…”
Section: Circulating Mirnasmentioning
confidence: 99%
“…For example, circulating miR- 155, 181a, 181b, 196a, 200a, 200b, and 212 were reported as significantly elevated in patients with chronic pancreatitis compared to healthy controls [75,80,110]. Li et al showed that serum levels of miR-200a and miR-200b are similar in patients with pancreatic cancer and pancreatitis, although they are elevated compared to healthy controls [91]. Interestingly, the miR-200 family can inhibit the transition from the epithelium to mesenchymes and therefore may play a direct signaling role [98].…”
Section: Circulating Mirnasmentioning
confidence: 99%